Nintedanib inhibits fibroblast activation and ameliorates fibrosis in preclinical models of systemic sclerosis - Huang, Jingang; Beyer, Christian; Palumbo-Zerr, Katrin; Zhang, Yun; Distler, Alfiya; Gelse, Kolja; Distler, Oliver; Schett, Georg; Wollin, Lutz; Distler, Jörg; Ramming, Andreas (Annals of the Rheumatic Diseases, 2015)
Nintedanib is a tyrosine kinase inhibitor that has recently been shown to slow disease progression in idiopathic pulmonary fibrosis in two replicate phase III clinical trials. The aim of this study was to analyse the antifibrotic effects of nintedanib in preclinical models of systemic sclerosis (SSc) and to provide a scientific background for clinical trials in SSc.The effects of nintedanib on migration, proliferation, myofibroblast differentiation and release of extracellular matrix of dermal fibroblasts were analysed by microtitre tetrazolium and scratch assays, stress fibre staining, qPCR and SirCol assays. The antifibrotic effects of nintedanib were evaluated in bleomycin-induced skin fibrosis, in a murine sclerodermatous chronic graft-versus-host disease model and in tight-skin-1 mice.Nintedanib dose-dependently reduced platelet-derived growth factor-induced and transforming growth factor-?-induced proliferation and migration as well as myofibroblast differentiation and collagen release of dermal fibroblasts from patients with and healthy individuals. Nintedanib also inhibited the endogenous activation of SSc fibroblasts. Nintedanib prevented bleomycin-induced skin fibrosis in a dose-dependent manner and was also effective in the treatment of established fibrosis. Moreover, treatment with nintedanib ameliorated fibrosis in the chronic graft-versus-host disease model and in tight-skin-1 mice in well-tolerated doses.We demonstrate that nintedanib effectively inhibits the endogenous as well as cytokine-induced activation of SSc fibroblasts and exerts potent antifibrotic effects in different complementary mouse models of SSc. These data have direct translational implications for clinical trials with nintedanib in SSc.
EVALuna2:13086